Tryptophan hydroxylase polymorphism and suicidality in unipolar and bipolar affective disorders: a multicenter association study - Souery, Daniel; Van Gestel, Sophie; Massat, Isabelle; Blairy, Sylvie; Adolfsson, Rolf; Blackwood, Douglas; Del-Favero, Jurgen; Dikeos, Dimitris; Jakovljevic, Miro; Kaneva, Radka; Lattuada, Enrico; Lerer, Bernard; et al. (Biological psychiatry (1969), 2001)
%Background:Being the rate-limiting enzyme in the biosynthesis of serotonin, the tryptophan hydroxylase gene (TPH) has been considered a possible candidate gene in bipolar and unipolar affective disorders (BPAD and UPAD). Several studies have investigated the possible role of TPH polymorphisms in affective disorders and suicidal behavior. Methods:The TPH A218C polymorphism has been investigated in 927 patients (527 BPAD and 400 UPAD) and their matched healthy control subjects collected within the European Collaborative Project on Affective Disorders. Results:No difference of genotype distribution or allele distribution was found in BPAD or UPAD. No statistically significant difference was observed for allele frequency and genotypes counts. In a genotype per genotype analysis in UPAD patients with a personal history of suicide attempt, the frequency of the C–C genotype (homozygosity for the short allele) was lower in UPAD patients (24%) than in control subjects (43%) (χ 2 = 4.67, p = .03). There was no difference in allele or genotype frequency between patients presenting violent suicidal behavior ( n = 48) and their matched control subjects. Conclusions:We failed to detect an association between the A218C polymorphism of the TPH gene and BPAD and UPAD in a large European sample. Homozygosity for the short allele is significantly less frequent in a subgroup of UPAD patients with a history of suicide attempt than in control subjects.